Experiências e sentido da participação juvenil na contemporaneidade: um estudo do Levante Popular da Juventude na cidade de Sorocaba-SP - Vigentin, Rafael (2016)
This paper analyzes the participations ways in a social movement of young people in Sorocaba city. It aims to contribute to the discussions about the young people participation and to reflect about educational respect processes that occur in these spaces. The research has been taken place for two years and it was used qualitative method, and it was observed the young people relation with the movement and the movement with the city. The bibliographic research is based on, specially, authors that study about sociology during the youth, bringing back the historical construction what youth is about, the relation between young people and society, the social representation and their attitude as social and historical subjects. It was analyzed the relation of young people with the politics, the difficulties about being recognized as political authors and some of their main actions through the history. It was done an analyze about the most present participation ways, considering, mainly, in the new collective actions, that assume characteristics of more fluid and horizontal organization, in nets and with strong dialogue with cultural aspects. We present a brief story about the Levante Popular no Brasil, the context and how it begot, its structure of organization and its main actions through the country, followed by the story of the movement in Sorocaba city, describing its main acts, its working dynamic, but also its conflicts and contradictions. Finally, We tried to understand the participation sense, analyzing its life trajectory, the coming to the political life and the relation of the young people with the movement, noticing that the sense of participating of a social movement is not only presented by ideological politics, but by the movement of constituting a space for friendship, construction of identities and sociability.